Why do Universities Rankings have Such Different Lists? - Sobral, Sónia Rolland (2021)
University rankings feature lists of higher education institutions ranked by item and weight. As they are available in the internet, they can be consulted by anyone wishing to find the best universities: students who want to enter higher education, teachers and researchers looking for new positions and governments/investors who want to fund the best. The lists are easy to consult and available to everyone. There are different classifications which are published: some are global, some are subdivided by areas, and others are only for one country. The results are very different from each other because they follow different systems. Many of the rankings have a huge number of Asian (mainly Chinese) universities in top positions while others consist mostly of American universities. This article compares the lists of computer science universities that appear in the rankings and analyzes the criteria for creating each of these rankings. Our goal is to understand why there are so many differences and which rankings favor each type of investigation. There is a direct relationship between the massive presence of top Asian universities and the total dependence on WebOfScience publications. The same is not true when the data source is the Scopus database.